Estudos psicofarmacológicos pré clínicos do 3-fenil-5-(4-metilfenil)-imidazolidin-2,4-diona (hpa-05) em camundongos - Maia, Ana Karina Holanda Leite (2013)
Heterocyclic compounds are found in many drugs with several therapeutic purposes, particularly in hydantoin derivatives. These derivatives, such as imidazolidine pharmaceuticals are employed as: anticonvulsants, cicatrizants, muscle relaxants, antimicrobials and antitumorals. Previous studies, using behavioral methodologies, have demonstrated that HPA-05 (3-phenyl-5-(4-methylphenyl) imidazolidine-2,4-dione) presented depressant actions on the CNS (Central Nervous System) with indications such as antinociceptives. These results have guided this work to a better study of the therapeutic activity of HPA-05 in pain relief. The dose of 200 mg/Kg of HPA-05, through i.p., does not involve the participation of K+ATP receptors in its mechanisms of action, neither GABAA receptors, it is not exerted by the cholinergic pathway and also does not involve the glutamatergic pathway, since the treatment with the substance under study does not reduce the duration of paw licking at any phases in the formalin test. The pretreatment of the animals with L-arginine was capable of reversing the antinociceptive effect of HPA-05 in the first phase of the formalin test, which involves the dopamine D2 receptors in the second phase and the interaction of caffeine with HPA-05, showing a reversion of the antinociceptive effect of HPA-05 in the first phase of the formalin test. The results with HPA-05 were effective in inhibiting the latency of convulsions induced by pentylenetetrazol and by auricular electroshock, what indicates to show profile of anticonvulsant drugs in these tests. In the Elevated Plus Maze test, it has not been observed any behavioral modification indicating a possible anxiolytic effect. In the peritonitis induced by carrageenan, there was a reduction in the levels of leukocytes and neutrophils in the intraperitoneal cavity of the treated animals, demonstrating the anti-inflammatory activity of HPA-05. The results shown in this study have evidenced a promising effect of HPA-05 as an analgesic, anti-inflammatory and anticonvulsant agent.